Analysis of Fear of Missing out Phenomena in Adolescent Social Interaction in the Digital Era - Khansa Meradaputhi; Nadia Aulia Nadhirah; Ipah Saripah (Journal of Education and Counseling (JECO), 2022)
This study aims to analyze the Fear of missing out on the social interactions of adolescents in the digital era. The research method used in this research is qualitative research, a literature study using and identifying books, journals, and articles. The digital era has enabled new forms of social interaction based on electronic information networks. From this social interaction,t a phenomenon called Fear of missing out (FOMO) arises. FOMO is the Fear of losing precious moments of individuals or other groups where the individual could be present. FOMO is the driving force behind the Internet, and social media use. Low life satisfaction can cause high FOMO due to frequent access to the Internet. In this case, the role of the Guidance and Counseling Teacher is very much needed, bearing in mind that teacher guidance is educational counseling that helps students become independent, develop their potential, and solve problems they experience in the school environment and outside of school. The role/efforts made by guidance and counseling teachers are to provide individual counseling to students who depend on the Internet and FOMO so that they can change their behavior for the better.